Pengaruh Pemberian Biskuit Tepung Belut dan Tepung Mocaf Terhadap Kadar Hemoglobin pada Ibu Hamil Anemia di Puskesmas Ngulak Kecamatan Sanga Desa - Putri, Balqis Ruwana; Rotua, Manuntun; Muzakar, Muzakar; Eliza, Eliza (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2022)
Background:Anemia in pregnant women is one of the risk factors for maternal and child mortality. Lack of iron intake for a long time causes a person to experience a decrease in hemoglobin levels. Pregnant women who suffer from anemia need snacks to help meet their nutritional needs and control Hb levels in the blood. Eel flour and mocaf flour contain high iron content so that the manufacture of spinach leaf flour biscuits and seluang fish meal is expected to be a snack with good nutritional value for pregnant women who suffer from anemia. Purpose : The purpose of this study was to determine the effect of giving biscuits with eel flour and mocaf flour on hemoglobin levels in anemic pregnant women at the Ngulak Public Health Center, Sanga Desa District. Methods: This study used a quasi-experimental design with a two-group pre-test and post-test research design. The population in this study were all pregnant women with anemia as many as 83 people and the research sample as many as 60, 30 people in the treatment group and 30 comparisons taken by purposive side. Analysis of the data used is using the t-dependent and t-independent test. Results:The results of the t-dependent test showed that there was a difference in hemoglobin levels before and after the intervention, the average increase in the respondent's hemoglobin level was 1.40 g/dl in the treatment group, p = 0,000 and an increase of 0,66 g / dl in the comparison group, p = 0,000. Meanwhile, the results of the independent t-test were p = 0,000, meaning that there was a difference between the hemoglobin levels in the treatment group and the comparison group. Conclusion:The provision of eel flour biscuits and mocaf flour had an effect on hemoglobin levels in anemic pregnant women at the Ngulak Public Health Center, Sanga Desa District